Anatomical and Histological Study of Thyroid Gland in Weasel (Herpestes javanicus) (E.Geoffroy saint.Hilaire,1818) - A. Al-Aamery, Rana; A.M. Dauod, Hussain (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study aimed to investigate the morphological description and histological  structure of  thyroid gland in Herpestes javanicus . The results revealed that thyroid gland in adult Herpestes javanicus is located in the neck region just below the larynx and attached to the trachea . Histological study revealed that thyroid gland  in H. javanicus surrounded by a capsule of losse connective tissue and the thyroid gland mainly formed from follicles within different sizes. The results showed that the follicle consists of three compenets represented by follicular lining cells, basal parafollicular cells and the colloid. Microscopical examination revealed that the follicular lining  tissue is either to be simple squamous or simple cuboidal epithelial tissue . The results also showed that the parafollicular cells (C-cells) are spherical, oval and even polygonal, and are located either interfollicular or intrafollicular.